2006
DOI: 10.1109/tec.2005.858094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Surface Permanent Magnet Machines With Fractional-Slot Concentrated Windings

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(80 citation statements)
references
References 29 publications
0
77
0
Order By: Relevance
“…PM based machines and SRM drives typically utilise fractional slot-concentrated windings (FSCW) due to their inherent advantages [11]. Many PM machine designs have been presented [12,13] with one IM being presented [14] and SRM The authors are with the Power Electronics, Machines and Drives Research Group, School of Electrical and Electronic Engineering, Newcastle University, Newcastle-Upon-Tyne, NE1 7RU, UK (e-mail: c.m.spargo@ncl.ac.uk).…”
Section: Introductionmentioning
confidence: 99%
“…PM based machines and SRM drives typically utilise fractional slot-concentrated windings (FSCW) due to their inherent advantages [11]. Many PM machine designs have been presented [12,13] with one IM being presented [14] and SRM The authors are with the Power Electronics, Machines and Drives Research Group, School of Electrical and Electronic Engineering, Newcastle University, Newcastle-Upon-Tyne, NE1 7RU, UK (e-mail: c.m.spargo@ncl.ac.uk).…”
Section: Introductionmentioning
confidence: 99%
“…The rated data of the motor with ROTOR 1 are summarized in Table I. The prototype was manufactured with a conventional stator core, made of silicon-steel laminations, as well as a standard three-phase star-connected winding [23]. The slots are skewed aiming to reduce the pulsation in the airgap flux density distribution.…”
Section: The Prototype Motormentioning
confidence: 99%
“…Motivation for concentrated winding is to provide magnetic isolation between two sets of stator winding. It can be shown that each concentrated coil around any stator tooth has an independent magnetic circuit [1] and it does not interfere magnetically with any other coils around the stator.…”
Section: B Concentrated Dual Winding Machine Structuresmentioning
confidence: 99%
“…Permanent magnet synchronous machines (PMSM) with concentrated winding topologies have recently become popular due to simpler and more compact structure as well as some operational advantages such as wider flux weakening range and higher torque output [1,2,8]. Furthermore magnetic isolation feature between coils, which naturally comes with concentrated winding topology, presents some opportunities such as better fault tolerance [3,4] and multi tasked operation as required by some accessory drive system applications in HEVs.…”
Section: Introductionmentioning
confidence: 99%